CYP2B6*6 allele and age substantially reduce steady‐state ketamine clearance in chronic pain patients: impact on adverse effects. (1st June 2015) - Li, Yibai; Jackson, Kate A.; Slon, Barry; Hardy, Janet R.; Franco, Michael; William, Leeroy; Poon, Peter; Coller, Janet K.; Hutchinson, Mark R.; Currow, David C.; Somogyi, Andrew A.
<x xml:space="preserve">Abstract</x> Aims Ketamine analgesia is limited by low intrinsic efficacy compounded by large interindividual variability in drug responses, possibly due to the heterogeneity in drug concentration. The CYP2B6*6 allele is associated with substantially reduced ketamine metabolism in vitro and, therefore, may affect ketamine clearance. Our aims were to examine the impact of the CYP2B6*6 allele on ketamine plasma clearance and on adverse effects in chronic pain patients. Methods CYP2B6 genotypes were identified in 49 chronic pain patients who received 24 h continuous subcutaneous infusions of ketamine. Steady‐state plasma concentrations of ketamine (Css, k) and norketamine (Css, nk) were determined using HPLC. Results The median plasma clearance of ketamine after 100 mg 24 h–1 dose was significantly lower in patients with the CYP2B6*6/*6 (21.6 l h–1) and CYP2B6*1/*6 (40.6 l h–1) genotypes compared with patients with the CYP2B6*1/*1 genotype (68.1 l h–1, P < 0.001). The ketamine : norketamine plasma metabolic ratio was significantly higher in patients with the CYP2B6*6/*6 genotype than in those with the CYP2B6*1/*6 and the CYP2B6*1/*1 genotypes (P < 0.001). Patients who experienced adverse effects had lower plasma clearance (45.6 l h‐1) than those who did not (52.6 l h‐1, P = 0.04). The CYP2B6*6 genotype and age, and their combined impact explained 40%, 30% and 60% of the variation in Css, k, respectively. Similar results were observed after higher doses. Conclusions The CYP2B6*6 allele is associated with a substantial decrease in steady‐state ketamine plasma clearance in chronic pain patients. The decreased clearance and resultant higher plasma concentrations may be associated with a higher incidence of ketamine adverse effects.